The evolution of social health insurance in Vietnam and its role towards achieving universal health coverage - Quynh Ngoc Le (Health Policy Open, 2020)
Our research examines the development of social health insurance (SHI) in Vietnam between 1992 and 2016 and SHI's role as a financial mechanism towards achieving universal health coverage (UHC). We reviewed and analysed legislation from the Government of Vietnam (GoV) and performance data from the GoV and the World Bank. Stages of development were identified from legislative change leading to change in SHI functioning as a public financing mechanism: revenue collection, pooling of risk, and purchasing. Movement towards UHC was assessed relative to: population coverage, benefit coverage, and financial protection. Vietnam has implemented SHI through five stages: Stage I (1992–1998), Stage II (1998–2005), Stage III (2005–2008), Stage IV (2008–2014), and Stage V (2014 onwards). Coverage has widened from a compulsory scheme for civil servants and pensioners and a voluntary scheme for others, to a scheme that targets the entire population. However, UHC has not been achieved with 19% of the population uninsured in 2016 and high out-of-pocket payments. The benefit package includes a wide range of services and many expensive medications and considered to be generous. It is recommended that Vietnam focus on improving population coverage rather than further expanding the benefit package to achieve UHC.